Impact of High-Altitude Hypoxia on Early Osseointegration With Bioactive Titanium - Wang, Yarong; Gan, Zekun; Lu, Haibin; Liu, Ziyi; Shang, Peng; Zhang, Jian; Yin, Wuwei; Chu, Hongxing; Yuan, Renlei; Ye, Yingxin; Chen, Pei; Rong, Mingdeng (Frontiers in Physiology, 2021)
Objectives: This study aimed to investigate the osseointegration of different bioactive titanium surfaces under either normoxic or high-altitude hypoxic environments. Methods: Titanium implants were subjected to two different surface treatments: (1) sanding, blasting, and acid etching to obtain a rough surface, and (2) extensive polishing to obtain a smooth surface. Changes in the morphology, proliferation, and protein expression of osteoblasts on the rough and smooth surfaces were examined, and bone formation was studied through western blotting and animal-based experiments. Results: A hypoxic environment and rough surface of titanium implants promoted the osteogenic differentiation of osteoblasts and activated the JAK1/STAT1/HIF-1α pathway in vitro. The animal study revealed that following the insertion of implants, bone repair at high altitudes was slower than that observed at low altitudes (i.e., in plains) at 2 weeks, but that bone formation was not significantly different at 4 weeks. Conclusions: Our findings indicate that dentists should exert more caution with regard to early osseointegration in patients living in high-altitude environments and that the effect of hypoxia can be alleviated by using dental implants with a rough surface.